English Adjectives and Estonian Nouns: Looking for Agreement? - Bahtina, Daria; Kask, Helin; Verschik, Anna (Frontiers in Psychology, 2021)
This study investigated how speakers of Estonian as L1 with varying degree of proficiency in English judge grammaticality of bilingual constructions English adjective + Estonian noun from the point of view of adjective agreement. Estonian is rich in inflectional morphology, and adjectives agree with nouns in case and number. The empirical evidence from English-Estonian bilingual speech shows that agreement is not always the case even when an English adjective fits into Estonian declension system. It is hypothesised that the higher proficiency in/exposure to English is, the higher is the acceptability of bilingual adjective phrases, and (non-)agreement does not play a role. To test this, an experiment was designed where the test corpus of 108 sentences consisted of real and constructed examples, both in agreement and non-agreement condition. Real sentences came from fashion and beauty blogs and vlogs. The test was administered online and the participants were asked to rate adjective acceptability. The hypothesis was confirmed: increased proficiency in English, together with younger age, had a positive correlation with acceptability of all adjective types, independent of adjective (non-)agreement. Residence and birthplace had a small effect on acceptability of some adjective types. Whether sentences were real or constructed, had only a minor effect. Male participants tended to assess real sentences lower, probably because of the topic typical for female blogs. Monosyllabic consonant-ending adjectives were exceptional, as their assessment did not depend on any factor. All in all, the study demonstrated that grammaticality judgment among the native speakers of the same L1 differs because of different degrees of bilingualism, and structural factors, such as compatibility with Estonian declension system, are not decisive. Thus, it is not clear what an ideal native speaker is.